Syndrome of inappropriate antidiuretic hormone secretion in a patient with a Nodular Lymphocyte-Predominant Hodgkin Lymphoma. A case report and review of literature - Ivonne Salcedo; Alvaro Aguayo; Javier Zuñiga (Journal of Hematology and Oncology Research, 2015)
Syndrome of inappropriate antidiuretic hormone secretion (SIADH) is a known side effect of several oncology drugs, but it is rarely seen secondary to vinblastine with only a few cases reported worldwide. Herein we present a patient with nodular lymphocyte-predominant Hodgkin disease that developed a severe acute hyponatremia seven days after her first cycle of chemotherapy with R-ABVD. After fluid restriction, symptoms and concentration of blood sodium were restored. After a comprehensive review of the literature vinblastine was thought to be the cause and avoided in the second infusion of chemotherapy without recurrence of the SIADH.
Keywords: lymphoma